Argemone mexicana decoction for the treatment of uncomplicated falciparum malaria. - Willcox, M; Graz, B; Falquet, J; Sidibé, O; Forster, M; Diallo, D (2007)
A prospective, dose-escalating, quasi-experimental clinical trial was conducted with a traditional healer using a decoction of Argemone mexicana for the treatment of malaria in Mali. The remedy was prescribed in three regimens: once daily for 3 days (Group A; n=23); twice daily for 7 days (Group B; n=40); and four times daily for the first 4 days followed by twice daily for 3 days (Group C; n=17). Thus, 80 patients were included, of whom 80% were aged<5 years and 25% were aged<1 year. All presented to the traditional healer with symptoms of malaria and had a Plasmodium falciparum parasitaemia>2000/microl but no signs of severe malaria. The proportions of adequate clinical response (ACR) at Day 14 were 35%, 73% and 65% in Groups A, B and C, respectively (P=0.011). At Day 14, overall proportions of ACR were lower in children aged<1 year (45%) and higher in patients aged>5 years (81%) (P=0.027). Very few patients had complete parasite clearance, but at Day 14, 67% of patients with ACR had a parasitaemia<2000/microl. No patient needed referral for severe disease. Only minor side effects were observed. Further research should determine whether this local resource could represent a first-aid home treatment in remote areas.